Deposition conditions and critical influence of organic additives on the structure and morphology of bismuth coatings - Tishkevich, Daria I.; Grabchikov, Sergey S.; Tsybulskaya, Ludmila S.; Shendyukov, Vladislav S.; Perevoznikov, Sergey S.; Poznyak, Sergey K.; Trukhanov, Alexey V. (Journal of the Belarusian State University. Chemistry, 2018)
XRD analysis showed that bismuth coatings formed from perchlorate electrolyte have a rhombohedral type of crystal lattice, the most intense reflex of Bi is (012). The number of organic additives adding into the electrolyte leads changing in the texture of the coatings growth, for example, in presence of acridine yellow and safranin violet, the most intense Bi reflex becomes (110). Surface morphology investigation using a scanning electron microscope showed that coatings obtained without organic additives, as well as in the presence of safranin violet, have the lager crystallite sizes (tens of microns) with different growth textures. The crystallite sizes decrease in the presence of resorcinol and synthanol with the same Bi growth texture (012). The most fine-grained, dense and uniform coatings were obtained with simultaneous syntanol and resorcinol adding into the electrolyte.
Keywords: electrodeposition; bismuth; perchloric electrolyte; organic additives; coatings